PP.17.08: AUSCULTATORY BLOOD PRESSURE MESUREMENT UNDERSTIMATED BLOOD PRESSURE VALUES COMPARED TO OSCILOMETRIC. (June 2015) - Lopez-Rivera, J.; Scrocchi, S.; Lopez, S.; Suarez, F.; Pereira, E.
Abstract : Objective: Arterial hypertension is the main risk factor attributable to cardiovascular morbidity and mortality. In population, studies have shown that there are a linear and continuous correlation between the increase blood pressure (BP) and risk of a coronary event, stroke, heart failure, renal failure. Most epidemiological studies in concentrated human groups have based hypertension with auscultatory BP measurement, even though guidelines recommend an oscillometric measurement, for diagnosis of hypertension, is also known that human group's agglomerates may have a greater possibility of observed inadequate variability with auscultatory method. Figure. No caption available. Design and method: Cross-sectional study was conducted in a mall, where prior knowledge informed people are taking their blood pressure (BP), on 2 occasions, with a difference of five minutes between the two measurements, with auscultatory method, a Riester mercury sphygmomanometer and an oscillometric method with a OMRON HEM 907, in order to classifying the population as hypertensive or normotensive if BP was equal to or greater than 140/90 mm Hg or less respectively, and evaluate BP between the first and second take, both systolic and diastolic component, auscultatory and oscillometric method. It was used an statistical analysis package software SPS 19, and Student t test was performed for parametric variables correlated with a confidence interval of 95%. Results: 151 people were surveyed, 56.96% women and 43.04% men, mean age of 52.62 years, range between 18–81 years, 51.3% had no regular employment, 46% did not own housing and 62% had secondary and university education. The systolic mean value was 123, 10 mm Hg by oscillometric method and 117, 6 by auscultatory method, the difference between both systolic were 5, 48 mm Hg, P < 0, 05, and to diastolic no were significance Conclusions: The systolic values were underestimated by auscultatory method non diastolic blood pressure when compare auscultatory and oscillometric technique. Recommended an oscillometric measurement to avoid underestimated BP systolic values.